Influencing Factors Injectable Kb Acceptor No Choose Method Contraception Long Period At The Clinic Bertha Primary 2022 - Bernadetta Ambarita; Artha Sigalingging (Sean Institute, 2022)
Tool Injectable contraception is hormonal contraceptives containing the hormone progesterone. Hormone this similar with natural hormones woman . that is progesterone and could stop ovulation . Usually injectable KB conducted in the body certain . Destination researcher for describe influencing factors KB injection acceptor to election tool contraception Method Period length . Method study descriptive , for describe influencing factors KB injection acceptor in election method Period length . Sample this as many as 25 respondents with technique accidental sampling . Location study it's at the clinic Primary Bertha on month may 2022. Results study this prove of 25 injectable family planning acceptors that Influencing factors injectable family planning acceptors who choose Method Contraception Period Long Is Factor knowledge may oritas enough 18 respondents (72%) and socio- cultural factors with majority support 20 respondents (80%) and based on majority factor Support husband as many as 21 respondents (84%) and majority factor source information based on power health respondent as much as 20 (80%). Could concluded that Factor Knowledge,Factor Social Culture, Factor Support husband, Factor Source information clinic primary Bertha no Influence election method period length . Based on a lot delivery clinic pratama Bertha energy Health could to do visit about explanation contraception period Long to mother the breath that will visited moment want to bathing baby patient.energy Health at the clinic primary Bertha can explain type type of MKJP or metode contraception period Long to mother postpartum.and telling you to mother benefit use MKJP.yang where very use of MKJP good on mother who wants postpone pregnancy with long term